Chinese Diaspora in Canada: Historical Contexts, Socio-Economic Contributions, and Policy Impacts - Rasulov, Ikhtiyor (Kirana Publisher (KNPub), 2025)
This study examines the Chinese diaspora in Canada, focusing on historical contexts, immigration patterns, socio-economic contributions and the impact of government policies. Using a methodological approach that includes historical analysis and data visualisation, key events such as the Chinese Immigration Act of 1885 and the Chinese Exclusion Act of 1923 are examined. The results show that Chinese Canadians have made a significant contribution to Canada’s economic development through labour, education and entrepreneurship, despite legal barriers and problems with credential recognition. Using the concept of “double diaspora,” the study emphasises the transnational mobility and complex identities of Chinese Canadians. Policy changes, including the repeal of exclusionary laws and economic immigration programmes, have enabled greater integration. This study offers valuable insights into the resilience and contributions of the Chinese diaspora and provides perspectives for researchers, policy makers and the public.